2016
DOI: 10.18632/oncotarget.10835
|View full text |Cite
|
Sign up to set email alerts
|

The application of mRNA-based gene transfer in mesenchymal stem cell-mediated cytotoxicity of glioma cells

Abstract: Since the tumor-oriented homing capacity of mesenchymal stem cells (MSCs) was discovered, MSCs have attracted great interest in the research field of cancer therapy mainly focused on their use as carries for anticancer agents. Differing from DNA-based vectors, the use of mRNA-based antituor gene delivery benefits from readily transfection and mutagenesis-free. However, it is essential to verify if mRNA transfection interferes with MSCs' tropism and their antitumor properties. TRAIL- and PTEN-mRNAs were synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…FITC-labeled mouse anti-human antibodies against CD34, CD44, CD73, CD90 and CD105 were used to identify surface antigens by flow cytometry. CD44, CD73, CD90 and CD105 were used as markers of hMSCs and CD34 was used as marker for hematopoietic stem cells [21]. We found that CD44, CD73, CD90 and CD105 were all positively expressed in hMSCs while CD34 was negatively expressed, which implies the successful isolation and culture of hMSCs (Figure 6A).…”
Section: Resultsmentioning
confidence: 90%
“…FITC-labeled mouse anti-human antibodies against CD34, CD44, CD73, CD90 and CD105 were used to identify surface antigens by flow cytometry. CD44, CD73, CD90 and CD105 were used as markers of hMSCs and CD34 was used as marker for hematopoietic stem cells [21]. We found that CD44, CD73, CD90 and CD105 were all positively expressed in hMSCs while CD34 was negatively expressed, which implies the successful isolation and culture of hMSCs (Figure 6A).…”
Section: Resultsmentioning
confidence: 90%
“…In vitro synthesis of Luc-mRNA and TRAIL-mRNA Luc-mRNA and TRAIL-mRNAs were synthesized in vitro as previously described [6]. Brie y, the human 5'UTR with Kozak sequence and 3'UTR sequence were commercially synthesized by Integrated DNA Technologies (Coralville, Iowa) and sub-cloned into pcDNA3.3.…”
Section: Methodsmentioning
confidence: 99%
“…The cell viability was detected by real-time assessment by the xCELLigence cell analyzer (RTCA, Roche, USA) as previously described [6]. A volume of 100 ÎŒl of DBTRG-Luc cell suspension (5 × 10 3 cells) was seeded in E-Plate 16.…”
Section: Viability Assay Of Dbtrg-luc Glioma Cellsmentioning
confidence: 99%
“…A recent study using lentiviral transductions showed that human umbilical cord MSCs expressing interleukin-18 inhibit the proliferation and metastasis of breast cancer in mice (Liu et al, 2018). Genetically engineered MSCs with TRAIL have also shown strong anti-tumor activity in different types of cancer (Ciavarella et al, 2012;Fakiruddin et al, 2014;Guo et al, 2016;Jiang et al, 2016). In a fascinating study, X. Jiang and colleagues developed a non-viral method using nanoparticles to produce human MSCs engineered to express the suicide protein TRAIL for targeting and eradicating intracranial gliomas in mice (Jiang et al, 2016).…”
Section: Mscs As Carriers Of Anti-cancer Payloadsmentioning
confidence: 99%
“…For instance, Bone Morphogenetic Protein 4 (BMP4)expressing MSCs were found to efficiently suppress tumor growth and prolong survival of glioma-bearing mice (Li et al, 2014;Mangraviti et al, 2016). Similarly, MSCs modified to express the tumor-suppressor gene Phosphatidylinositol 3,4,5-Trisphosphate 3-Phosphatase (PTEN) induced cytotoxicity of glioma cells (Guo et al, 2016).…”
Section: Mscs As Carriers Of Anti-cancer Payloadsmentioning
confidence: 99%